Taxonomy of subfamilies Melolonthinae and Rutelinae in Malaysia - Ameen Abdullah, Ali Mohammad (2016)
Most of the species in Scarabaeidae are economically important all over the world and especially in Southeast Asia. Hence, it is important to identify, construct keys and also develop a checklist of Malaysian Melolonthinae and Rutelinae. This study establishes the current taxonomical status of 15 species of these two subfamilies in Malaysia. A total of 320 specimens were collected from 10 states (Selangor, N. Sembilan, Melaka, Johor, Pahang, P. Pinang, Kedah, Perak, Sabah and Sarawak), 22 area and 72 sampling points. Four species recorded for the first time in Malaysia: Anomala shainica, Mimela malaise, Schoenherria vervex, Lepidiota leai. All genera and species have been described and illustrated. Taxonomic keys were constructed based on morphological characters particularly the mouth part, pronotum, elytra, front tibia and male genitalia. The latest checklist was developed for Malaysian Melolonthinae and Rutelinae. The total number of Melolonthinae species is 166 belonging to 22 genera and the total number of Rutelinae species is 165 belonging to 14 genera. Therefore this study successfully provides a taxonomical information on both subfamilies in Malaysia which will be a basic knowledge for further applied field studies.